Quantitative photoacoustic estimates of intervascular blood oxygenation differences using linear unmixing. Issue 1 (January 2021) - Bench, C; Cox, B
Abstract: The linear unmixing technique is an appealing method for estimating blood oxygen saturation (sO2 ) from multiwavelength photoacoustic tomography images, as estimates can be acquired with a straightforward matrix inversion. However, the technique can only rarely provide accurate estimates in vivo, as it requires that the light fluence at the voxels of interest is constant with wavelength. One way to extend the set of cases where accurate information related to sO2 can be acquired with the technique is by taking the difference in sO2 estimates between vessels. Assuming images are perfectly reconstructed, the intervascular difference in sO2 estimates is accurate if the error in the estimates due to the wavelength dependence of the fluence is identical for both. An in silico study was performed to uncover what kinds of conditions may give rise to accurate sO2 differences for a vessel pair. Basic criteria were formulated in simple tissue models consisting of a pair of vessels immersed in two-layer skin models. To assess whether these criteria might still be valid in more realistic imaging scenarios, the sO2 difference was estimated for vessels in more complex tissue models.